THE ROLE OF CHEMICAL ADMIXTURES IN THE PRODUCTION OF MODERN CONSTRUCTION MATERIALS: A COMPARATIVE STUDY OF INTERNATIONAL PRACTICES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes the role of chemical admixtures in the production of modern construction materials, their influence on physical and mechanical properties, and the global experience of their application. Today, chemical admixtures play a crucial role in the production of environmentally friendly, energy-efficient, and high-strength concretes. The study compares the practices of European countries, the USA, Japan, China, Korea, and CIS states, focusing on the use and efficiency of polycarboxylate-based superplasticizers, accelerators, retarders, air-entraining, and hydrophobic agents. The findings highlight that these admixtures significantly enhance concrete strength, durability, and frost resistance while reducing water absorption. The paper concludes with recommendations for developing admixtures suitable for Uzbekistan’s local climate and raw material base.